Densification Behavior, Phase Transition, and Preferred Orientation of Hot‐Pressed ZnS Ceramics from Precipitated Nanopowders. Issue 9 (3rd June 2016) - Li, Chaoyu; Pan, Yubai; Kou, Huamin; Chen, Haohong; Wang, Wei; Xie, Tengfei; Li, Jiang
Abstract : In this study, transparent ZnS ceramics were hot pressed from precipitated wurtzite nanopowders. Influences of sintering temperature on wurtzite‐to‐sphalerite phase transition and densification behavior have been investigated. Maximum sphalerite phase content and highest densification were simultaneously obtained in the sample hot pressed at 900°C with uniaxial pressure of 250 MPa for 2 h, which accounts for the highest transmittance above 55% and 70% in the range 2–5 μm and 5–13 μm, respectively. Preferred orientation of wurtzite grains in [002] direction paralleled to the press direction was also observed, which is supposed to be benefit to transmittance by reducing birefraction and second‐phase scattering. Furthermore, second‐phase scattering caused by wurtzite grains has been investigated. It is found that fine grains are conducive to hot‐pressed ZnS ceramics with high transmittance, especially in the short‐wavelength range.